2020
DOI: 10.15517/ijds.2020.41900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Denture Base Cleansers on Surface Roughness of Heat Polymerised Acrylic Materials with Different Curing Process

Abstract: Avoiding biofilm formation on dentures is associated with maintaining the surface properties of acrylic-based dentures. The aim of the study is to investigate the effects of two different cleaning agents (Corega and Klorhex 0.2% chlorhexidine gluconate) on surface roughness of the denture regarding efficacy of curing procedures. A total of sixty disc-shaped specimens were prepared with two different methods as long and short curing processes. The specimens were divided into subgroups according to the immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In total, 155 studies were excluded based on the exclusion criteria. Thus, 17 studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were included (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 155 studies were excluded based on the exclusion criteria. Thus, 17 studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were included (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [14,15,17,20,23,[26][27][28]30] reported no significant change in surface roughness, while seven studies [16,19,21,22,24,25,29] reported a significant increase in surface roughness after immersion in chemical denture cleansers. An increase in roughness after using alkaline peroxide has been reported in four studies [16,18,19,22]. In addition, Arbeláez et al (2020) [29] re-ported a significant increase in the surface roughness of resin samples immersed in 0.5% sodium hypochlorite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the observed tendency for the presence of C. albicans colonies/cells in the crystallized structures or traces after grinding is maintained, according to reports indicating that increased roughness may promote an increased degree of surface colonization [ 60 ]. This indicates that problems with the removal of microorganisms from prosthetic materials over time and their rapid recolonization after disinfection [ 19 , 61 ] may not be caused by the penetration of C. albicans into materials, but by the formation of surface microcracks or screeches due to daily use including cleaning or the impact of thermal cycles [ 62 , 63 , 64 ], which may be difficult to disinfect with cleaning agents. This supposition is supported not only by the currently obtained results, but also by the in vivo investigations by Taylor et al [ 65 ], in which the interior of the prosthetic materials was not penetrated.…”
Section: Discussionmentioning
confidence: 99%